How do you prove the identity \[\dfrac{{cosec \theta - 1}}{{\cot \theta }} = \dfrac{{\cot \theta }}{{cosec \theta + 1}}\]?
Answer
Verified
443.7k+ views
Hint:Start from the left hand side and multiply both numerator and denominator by \[cosec \theta + 1\]. Then use the trigonometric formula ${cosec ^2}\theta - {\cot ^2}\theta = 1$ to simplify it further and bring it in the form of the right hand side.
Complete step by step answer:According to the question, we have been given a trigonometric identity and we are asked to prove it.
The trigonometric identity is:
\[ \Rightarrow \dfrac{{cosec \theta - 1}}{{\cot \theta }} = \dfrac{{\cot \theta }}{{cosec \theta + 1}}{\text{ }}.....{\text{(1)}}\]
We’ll start with the left hand side and apply trigonometric formulas to convert it in the form of right hand side.
So we have:
\[ \Rightarrow {\text{LHS}} = \dfrac{{cosec \theta - 1}}{{\cot \theta }}\]
If we multiply both numerator and denominator by \[cosec \theta + 1\], we’ll get:
\[
\Rightarrow {\text{LHS}} = \dfrac{{cosec \theta - 1}}{{\cot \theta }} \times \dfrac{{cosec \theta + 1}}{{cosec \theta + 1}} \\
\Rightarrow {\text{LHS}} = \dfrac{{\left( {cosec \theta - 1} \right)\left( {cosec \theta + 1} \right)}}{{\cot \theta \left( {cosec \theta + 1} \right)}} \\
\]
We know an important algebraic formula as:
\[ \Rightarrow \left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}\]
Applying this formula in our trigonometric expression, we’ll get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{{{cosec }^2}\theta - 1}}{{\cot \theta \left( {cosec \theta + 1} \right)}}\]
Now, we have a trigonometric formula as given below:
$ \Rightarrow {cosec ^2}\theta - {\cot ^2}\theta = 1$
Separating terms in this formula, we have:
$ \Rightarrow {cosec ^2}\theta - 1 = {\cot ^2}\theta $
So putting this value of ${cosec ^2}\theta - 1$ in our above trigonometric expression, we’ll get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{{{\cot }^2}\theta }}{{\cot \theta \left( {cosec \theta + 1} \right)}}\]
On further simplification, \[\cot \theta \] will get cancel out from both numerator and denominator. Doing this we will get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{\cot \theta }}{{cosec \theta + 1}}\]
Now comparing this final expression with the expression in equation (1), we can conclude that:
\[ \Rightarrow {\text{LHS}} = {\text{RHS}}\]
Therefore this is how we prove this identity.
Note:
In this problem, we can also start from the right hand side and simplify it to bring it in the form of the left hand side. The solution will still be correct conceptually.
Some of the widely used trigonometric formulas are:
(1) ${\sin ^2}\theta + {\cos ^2}\theta = 1$
(2) ${\sec ^2}\theta - {\tan ^2}\theta = 1$
(3) ${cosec ^2}\theta - {\cot ^2}\theta = 1$
The last formula we have already used in the above problem.
Complete step by step answer:According to the question, we have been given a trigonometric identity and we are asked to prove it.
The trigonometric identity is:
\[ \Rightarrow \dfrac{{cosec \theta - 1}}{{\cot \theta }} = \dfrac{{\cot \theta }}{{cosec \theta + 1}}{\text{ }}.....{\text{(1)}}\]
We’ll start with the left hand side and apply trigonometric formulas to convert it in the form of right hand side.
So we have:
\[ \Rightarrow {\text{LHS}} = \dfrac{{cosec \theta - 1}}{{\cot \theta }}\]
If we multiply both numerator and denominator by \[cosec \theta + 1\], we’ll get:
\[
\Rightarrow {\text{LHS}} = \dfrac{{cosec \theta - 1}}{{\cot \theta }} \times \dfrac{{cosec \theta + 1}}{{cosec \theta + 1}} \\
\Rightarrow {\text{LHS}} = \dfrac{{\left( {cosec \theta - 1} \right)\left( {cosec \theta + 1} \right)}}{{\cot \theta \left( {cosec \theta + 1} \right)}} \\
\]
We know an important algebraic formula as:
\[ \Rightarrow \left( {a - b} \right)\left( {a + b} \right) = {a^2} - {b^2}\]
Applying this formula in our trigonometric expression, we’ll get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{{{cosec }^2}\theta - 1}}{{\cot \theta \left( {cosec \theta + 1} \right)}}\]
Now, we have a trigonometric formula as given below:
$ \Rightarrow {cosec ^2}\theta - {\cot ^2}\theta = 1$
Separating terms in this formula, we have:
$ \Rightarrow {cosec ^2}\theta - 1 = {\cot ^2}\theta $
So putting this value of ${cosec ^2}\theta - 1$ in our above trigonometric expression, we’ll get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{{{\cot }^2}\theta }}{{\cot \theta \left( {cosec \theta + 1} \right)}}\]
On further simplification, \[\cot \theta \] will get cancel out from both numerator and denominator. Doing this we will get:
\[ \Rightarrow {\text{LHS}} = \dfrac{{\cot \theta }}{{cosec \theta + 1}}\]
Now comparing this final expression with the expression in equation (1), we can conclude that:
\[ \Rightarrow {\text{LHS}} = {\text{RHS}}\]
Therefore this is how we prove this identity.
Note:
In this problem, we can also start from the right hand side and simplify it to bring it in the form of the left hand side. The solution will still be correct conceptually.
Some of the widely used trigonometric formulas are:
(1) ${\sin ^2}\theta + {\cos ^2}\theta = 1$
(2) ${\sec ^2}\theta - {\tan ^2}\theta = 1$
(3) ${cosec ^2}\theta - {\cot ^2}\theta = 1$
The last formula we have already used in the above problem.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE